2005
DOI: 10.1021/ja0540270
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Strategy for the Rapid Backbone Assignment of Membrane Proteins

Abstract: Investigations of membrane proteins pose one of the biggest current challenges in structural biology. Recent advances in protein production techniques based on cell-free transcription/translation methods have, however, opened new opportunities in this area. Here, we report an efficient protocol for the backbone assignment of membrane proteins as the first step of NMR-based structure determination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
72
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 11 publications
1
72
0
Order By: Relevance
“…Signal overlapping usually impede amino acid discrimination especially in CSL, therefore, the number of labeled aminoacids is reduced according to its occurrence in some CSL (Trbovic et al 2005;Wu et al 2006;Sobhanifar et al 2010;Löhr et al 2012). In the present study, we labeled all of the non-proline 19 amino acids, however, quantitative peak fitting used for decoding information in SiCode solved the signal overlapping issue as demonstrated.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Signal overlapping usually impede amino acid discrimination especially in CSL, therefore, the number of labeled aminoacids is reduced according to its occurrence in some CSL (Trbovic et al 2005;Wu et al 2006;Sobhanifar et al 2010;Löhr et al 2012). In the present study, we labeled all of the non-proline 19 amino acids, however, quantitative peak fitting used for decoding information in SiCode solved the signal overlapping issue as demonstrated.…”
Section: Discussionmentioning
confidence: 78%
“…As described above, conventional CSL schemes generally uses two SI-labeling levels, enabling that 1 bit information is contained in each labeled sample (Parker et al 2004;Shi et al 2004;Trbovic et al 2005;Staunton et al 2006;Wu et al 2006;Maslennikov et al 2010;Sobhanifar et al 2010;Hefke et al 2011;Krishnarjuna et al 2011;Jaipuria et al 2012; Maslennikov and Choe 2013). In the previously mentioned triple selective CSL approach (Löhr et al 2012), three SIlabeling types can be discriminated for both residues i and i -1: unlabeled, 15 N-labeled, or 2-13 C/ 15 N-labeled for the residue i and unlabeled, 1-13 C-labeled, or 1,2-13 C-labeled for the residue i -1, respectively, being considered that 1 trit (ternary digit) information is contained in each sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the high internal flexibility of an unfolded polypeptide chain leads to slow relaxation, thereby enabling the use of pulse sequences with more and longer transfer delays for resolving overlap (12), for large membrane proteins solubilized in micelles, only the most basic experiments yield enough sensitivity. In a recent publication we demonstrated that the resulting overlap problem can be overcome, allowing for the sequential backbone assignment of membrane proteins Ͼ200 aa (13,14). Our strategy was based on a two-step approach in which we first use standard triple-resonance experiments to obtain as many assignments as possible and then use a double-labeling scheme to select amino acid pairs with a two-dimensional version of the HNCO experiment to sequence-specifically identify additional amino acids (15)(16)(17).…”
mentioning
confidence: 99%